2011
DOI: 10.1021/jo102063s
|View full text |Cite
|
Sign up to set email alerts
|

Mild Transition-Metal-Free Amination of Fluoroarenes Catalyzed by Fluoride Ions

Abstract: Trimethylsilyl-protected heterocycles undergo N-C bond formation with a variety of electron-deficient fluoroarenes catalyzed by fluoride ions. This reaction avoids stoichiometric amounts of base and thus makes N-arylheterocycles accessible in a very mild and transition-metal-free way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 81 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The procedure is based on the reaction of readily available N-trimethylsilylamines with acid fluorides in the presence of catalytic fluoride ion. Formally, the fluoride ion reacts with the silylated amine to form a 'hypervalent' silicon species, 4 which readily decomposes to produce volatile TMSF and an amine anion intermediate, which is higher in energy and more nucleophilic/reactive than the corresponding free amine. Although often stable to water, and less reactive than acid chlorides toward alcohols, acid fluorides react efficiently with amines to give the expected amide products.…”
Section: Syn Thesismentioning
confidence: 99%
“…The procedure is based on the reaction of readily available N-trimethylsilylamines with acid fluorides in the presence of catalytic fluoride ion. Formally, the fluoride ion reacts with the silylated amine to form a 'hypervalent' silicon species, 4 which readily decomposes to produce volatile TMSF and an amine anion intermediate, which is higher in energy and more nucleophilic/reactive than the corresponding free amine. Although often stable to water, and less reactive than acid chlorides toward alcohols, acid fluorides react efficiently with amines to give the expected amide products.…”
Section: Syn Thesismentioning
confidence: 99%
“…1 ). In contrast, halogenated benzoic acid derivatives are easily functionalized through cross-coupling [ 4 5 ] or nucleophilic aromatic substitution reactions (S N Ar) [ 6 7 ]. Benzoic acids (e.g., 2 ) are relatively weak acids, even with highly electron-withdrawing substituents on the aromatic core [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 A theoretical study, using DFT methods, has used the relative stabilities of isomeric σ -adduct intermediates to predict regioselectivity patterns in the substitution of polyfluoroaromatics. 26 The catalysis by transition metals of cross-coupling reactions of polyfluoroarenes has been reviewed. 24 The regioselectivity of reaction of substituted pentafluorobenzenes by 1,2,3-benzotriazole has been shown to depend on the nature of the substituent, the base used, and also on the solvent, toluene or acetonitrile.…”
mentioning
confidence: 99%
“…There have been reviews of couplings catalysed by palladium 70 and by palladium in combination with copper. 74 Using palladium catalysis, arenes substituted with a 2-pyridylsulfinyl group have been shown to react with alkenes at the ortho positions which may lead to disubstituted products such as (26). 73 It has been shown that using a palladium-N-heterocyclic carbene catalyst, the reaction of aryl halides with Michael acceptors may result either in conjugate addition or Heck substitution, depending on the base used.…”
mentioning
confidence: 99%
See 1 more Smart Citation